2019
DOI: 10.37358/rc.19.9.7498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of the Treatment with Benfotiamine and Alpha-lipoic Acid in Distal Symmetric Painful Diabetic Polyneuropathy

Abstract: Distal symmetric painful diabetic neuropathy is the most frequent clinical form of diabetic neuropathy. The condition appears as a result of alteration of the structure and function of nervous fibres as a consequence of hyperglycaemia. Hyperglycaemia determines the metabolism of glucose on alterative pathways and generates increased oxidative stress, mechanisms that cause an accelerated apoptosis of the neurons and a high intensity of lipid peroxidation. Pathogenic treatment of diabetic neuropathy includes lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…CAD has several particularities in CKD consisting in high incidence, rapid progression, elevated prevalence of multi-vessel disease, and presence of vascular calcifications that interfere with proper stent expansion. Results regarding the high incidence of three-vessel CAD and LMCA in CKD patients were similar to other findings of similar studies, but they did not reach the statistically significant number due to the low number of patients and a single experimental centre [34,[37][38][39]. Revascularization with PCI or CABG is challenging.…”
Section: Discussionsupporting
confidence: 63%
“…CAD has several particularities in CKD consisting in high incidence, rapid progression, elevated prevalence of multi-vessel disease, and presence of vascular calcifications that interfere with proper stent expansion. Results regarding the high incidence of three-vessel CAD and LMCA in CKD patients were similar to other findings of similar studies, but they did not reach the statistically significant number due to the low number of patients and a single experimental centre [34,[37][38][39]. Revascularization with PCI or CABG is challenging.…”
Section: Discussionsupporting
confidence: 63%
“…Individuals with fast-food consumption also consume a high quantity of sweetened beverages (11). Nutrition interventions are effective measures to improve diet quality (12). One meta-analysis evaluating 14 studies carried out on college students demonstrated that nutrition education provided as lectures, web education or giving informative supplements, significantly improves nutrition knowledge and dietary practices (13).…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle changes have triggered the obesity epidemic; obesity is the main cause for metabolic syndrome because obesity generates insulin resistance and insulin resistance is associated with all the components of metabolic syndrome (7). Adipocytes are metabolically active cells generating different metabolites called adipokines that act at different levels, some of them increasing the risk of diabetes and cardiovascular disease such as C-reactive protein (CRP), tumour necrosis factor α (TNFα) and interleukin-6 (IL-6), plasminogen activator inhibitor-1 (PAI-1), some of them decreasing, at least theoretically, the risk of diabetes and atherosclerosis such as adiponectin (8).…”
Section: Introductionmentioning
confidence: 99%